An Acid/Base‐Regulated Recyclable Strategy for Homogeneous Cinchona Alkaloid‐Derived Primary Amine Organocatalysts in Aldol, Vinylogous Michael and Double‐Michael Cascade Reactions. Issue 26 (31st July 2015) - Wan, Jingwei; Zhao, Zhiwei; Wang, Falu; Ma, Xuebing
Abstract: A practical, recyclable strategy for homogeneous cinchona alkaloid‐derived primary amine organocatalysts was developed by controlling the solubilities in an aqueous/organic biphasic system through regulating the pH of the aqueous phase, effecting the protonation and deprotonation of primary amino, tertiary amino and pyridyl groups. By means of model aldol, vinylogous Michael and double‐Michael cascade reactions, the reusability of the organocatalysts epi ‐CDNH2, DeMe‐QNNH2 and H‐CDNH2 over three cycles was investigated in detail. It was found that the organocatalysts were highly effective with respect to catalytic performance, including the yields and stereoselectivities. Furthermore, the recovered organocatalysts in the tenth cycle retained similar excellent enantioselectivities to fresh organocatalysts. However, the formation of inactive intermediates between organocatalyst and reactants resulted in decreased yields. Abstract : A practical acid/base‐regulated recyclable strategy for cinchona alkaloid‐derived organocatalysts by means of protonation and deprotonation of primary and tertiary amine groups was developed and applied in asymmetric aldol, vinylogous Michael and double‐Michael cascade reactions.